A combined wave-dam-breaking model for rogue wave overtopping. (1st August 2015) - Hu, Zhe; Xue, Hongxiang; Tang, Wenyong; Zhang, Xiaoying
Abstract: Although great efforts have been devoted to revealing the formation mechanisms of rogue waves, the study of wave–structure interaction such as the green water phenomenon is still not sufficient. Since the traditional Ritter׳s solution of dam-breaking model gives improper estimations on the rogue wave overtopping, a combined wave-dam-breaking (CWDB) model is proposed. The CWDB model is deduced from the Ritter׳s solution, by including the influence of the rogue wave propagation as well as the delayed effect of the dam-breaking problem. Various rogue waves, which are based on the Peregrine breather solution of nonlinear Schrödinger (NLS) equation, are generated in a numerical wave flume. The rogue waves impinge onto a horizontal deck placed at the center part of the tank, creating green water on the deck surface. The CWDB model is validated by making comparisons with both numerical results and existing experimental measurements. Great improvement can be revealed by contrasting the results of the CWDB model with those of the Ritter׳s solution. Highlights: A CWDB model for the overtopping events caused by rogue waves is proposed. Significant improvement is achieved compared with the Ritter׳s solution. The CWDB model is efficient for both rogue waves and common waves. The CWDB model can be used for structure design and safety assessment.